2022
DOI: 10.1007/s00376-022-1409-7
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Topographic Complexity on Modeling Moisture Transport and Precipitation over the Tibetan Plateau in Summer

Abstract: The non-hydrostatic global variable resolution model (MPAS-atmosphere) is used to conduct the simulations for the South Asian Summer monsoon season (June, July, and August) in 2015 with a refinement over the Tibetan Plateau (TP) at the convection-permitting scale (4 km). Two experiments with different topographical datasets, complex (4-km) and smooth (60-km) topography, are designed to investigate the impacts of topographical complexity on moisture transport and precipitation. Compared with the observations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…Compared to U120 m, V16 km with higher horizontal resolution resolves more topographical complexity over the refined regions. Previous studies have suggested that the complex topography would result in an overall weakening effect on the near‐surface wind speed due to the orographic drag process and more heterogeneous spatial distribution due to resolved mountains and valleys (e.g., Li et al., 2022; Lin et al., 2018; Y. Wang et al., 2020; Zhang et al., 2020; Zhou et al., 2018). Figures 11b and 11e shows the difference in near‐surface wind speed between the V16 km‐EA/NA and U120 km experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to U120 m, V16 km with higher horizontal resolution resolves more topographical complexity over the refined regions. Previous studies have suggested that the complex topography would result in an overall weakening effect on the near‐surface wind speed due to the orographic drag process and more heterogeneous spatial distribution due to resolved mountains and valleys (e.g., Li et al., 2022; Lin et al., 2018; Y. Wang et al., 2020; Zhang et al., 2020; Zhou et al., 2018). Figures 11b and 11e shows the difference in near‐surface wind speed between the V16 km‐EA/NA and U120 km experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Please note that the mesh refinement is not only for improving dust modeling performance but also for better simulating the climatic effects of dust at higher resolution. At higher resolution, the complex topography can be better resolved, which is important for modeling near‐surface wind speed and the transport of air particles and moisture on a regional scale (e.g., Li et al., 2022; Zhang et al., 2020) (see Section 3.2.3). In addition, the interaction between dust and cloud‐precipitation‐radiation and its impacts on regional climate can be better simulated at higher horizontal resolutions (e.g., Lau et al., 2020; Sakaguchi et al., 2015; Xu et al., 2021; Zhao et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, uncertainty may also exist in the simulation. For instance, the overestimate of convective rainfall in the tropical Bay of Bengal and orographic precipitation in the southeastern Tibetan Plateau might introduce some uncertainty in the response of large-scale circulation to BB aerosols, which is strongly related to the cumulus convection parameterization scheme and the topographic complexity (Ma and Tan, 2009;Li et al, 2022). Therefore, further experiments at convection-resolved resolution need to be conducted to reduce such uncertainty.…”
Section: Delayed Effectmentioning
confidence: 99%
“…Zhu et al (2018) indicated that the convection-permitting forecasts of precipitation in China during the summer of 2013-2014 outperform global forecasts in terms of spatial distribution, intensity, and diurnal variation. With respect to regional climate simulation, previous studies have also demonstrated that convection-permitting resolution could significantly improve the simulation of characteristics, duration and diurnal variability of hourly precipitation (e.g., Kendon et al 2012, Kendon et al 2014, Ban et al, 2014, Gao et al 2017, Li et al 2022. Gao et al (2017) revealed that the convection-permitting simulations were more realistic in reproducing the observed spatial distributions and diurnal variability of precipitation than the simulations at 36 km resolution.…”
Section: Introductionmentioning
confidence: 98%